Learning About Race and Ethnic Diversity on Campus: Employee Perceptions from an Urban University - Larry G. Martin (Adult Education Research Conference, 2006)
The research project utilized a mixed method design to investigate the extent to which a large (i.e., 26,000 students) urban university has provided an accepting and accommodating environment for individuals from various racial and ethnic backgrounds; and to identify the race and ethnic diversity-related issues and concerns that currently exist among university employees.
Keywords: Diversity; postsecondary; race and ethnicity; organizational learning